A combined experimental and computational approach to evaluate microclimate control at the support surface interface. Issue 3 (August 2021) - Van Asten, J.G.M.V.; Fung, M.-T.; Oomens, C.W.J.; Bader, D.L.; Worsley, P.R.
Abstract: Temperature and humidity conditions at the interface between a support surface and the skin, termed microclimate, has been implicated in the development of pressure ulcers. Support surface technologies have been developed to control microclimate conditions, although only a few standard test methods exist to evaluate their performance. This study describes a combined experimental-computational approach to analyzing microclimate control systems. The study used a modified physical model protocol to evaluate two specific support surface systems involving a spacer fabric cover with i) no air flow and ii) an active fan. The physical model deposited moisture at a controlled rate for 25 min, and the microclimate conditions under the model and the surrounding area were monitored for 24 h. Using the experimental data as boundary conditions, a finite element model was developed using mass transport principles, which was calibrated using experimental results. Model inputs included mass density and mass diffusivity, resulting in an estimated absolute humidity change over time. The physical model tests revealed distinct differences between the support surfaces with and without active airflow, with the former having little effect on local humidity levels (RH>75% for 24hr). By contrast, there was a spatial and temporal change in microclimate with the active fan, with sensors positioned towards the source of airflow reaching ambient conditions within 24hr. The computational model was refined to produce comparable results with respect to both the spatial distribution of microclimate and the change in values over time. The combined experimental and computation approach was able to distinguish distinct difference in microclimate change between two support surface designs. The approach could enable the efficient evaluation of different mattress design principles to aid decision making for personalized support surface solutions, for the prevention of pressure ulcers. Highlights: A combined experimental and computational approach to assess microclimate. Simulations could accurately predict changes in humidity over time. Airflow and material choice are critical for microclimate control. This provide a platform to support design innovation of support surfaces.